Rectus sheath hematoma in patients receiving subcutaneous enoxaparin: A case series of five patients - Mendes, Diogo (2020)
Physicians must acknowledge the potential risk of RSH with enoxaparin. Switching home anticoagulation by enoxaparin upon hospital admission is common, but it may put patients at higher risk for RSH. Management guidelines are needed in this setting.